Prepared for retirement? The adequacy and distribution of retirement resources in England - James Banks; Carl Emmerson; Zoë Oldfield; Gemma Tetlow (Institute for Fiscal Studies (IFS), 2005)
This report provides new empirical evidence on the level and distribution of retirement saving in England. For the first time in recent years, we have been able to estimate accrued state and private pension wealth to include in our measures of retirement saving. We use new data on 4,687 individuals aged between 50 and the state pension age taken from the 2002-03 English Longitudinal Study of Ageing. Since there is little existing information on the distribution of accrued pension wealth in Britain, we begin by reporting the level and distribution of pension wealth. We move on to consider total wealth and the relationship between pension wealth and other components of total wealth such as housing and financial assets. We document people's retirement, longevity and inheritance expectations and how these differ across the wealth distribution, before concluding by presenting estimates of the fraction of our sample whose retirement resources appear to fall short of different possible benchmarks for 'adequate' retirement resources.
Keywords: 330